PEDAGOGY IN FINNISH HIGHER EDUCATION: A CASE EXAMPLE OF HÄME UNIVERSITY OF APPLIED SCIENCES - Carolina Carvalho; Mervi Friman; Seija Mahlamäki-Kultanen (Universidade Feevale, 2019)
ABSTRACT In the context of pedagogical development in higher education (HE) this research is a case study concerning Häme University of Applied Sciences (HAMK), in Finland. The focus of the study is to make visible the correspondence between the international and national higher education policy emphasis and an individual higher education institution. Ten thematic approaches in higher education pedagogy were identified in a content analysis of policy documents, and from earlier interviews in Finnish higher education institutes. The data for this study was gathered in subsequent interviews at HAMK and was compared with these ten thematic approaches. The results show how the national and institutional pedagogical emphasis correspond in the case of universities of applied sciences (UAS). The correspondence with the ten pedagogical emphases were classified as (1) strongly consolidated, (2) currently highlighted and (3) less emphasized. The conclusion is that it is challenging and complicated to apply pedagogical goals systematically considering the various attributes from a world in constant change. In-house prioritize needs awareness of strategy, negotiations, and co-operation. The main points for the successful pedagogical development are (1) prioritization of the emphasis, (2) systematic progress and quality assurance and (3) co-operation within the pedagogic actors. Keywords: Higher education. University of applied sciences. Pedagogy. Pedagogical strategy.      RESUMO No contexto do desenvolvimento pedagógico no ensino superior (ES), esta pesquisa é um estudo de caso sobre a Universidade de Ciências Aplicadas Häme (HAMK), na Finlândia. O foco do estudo é tornar visível a correspondência entre a ênfase da política de ensino superior internacional e nacional e uma instituição de ensino superior individual. Dez abordagens temáticas na pedagogia do ensino superior foram identificadas na análise de conteúdo de documentos políticos e entrevistas em institutos de ensino superior finlandeses. Os dados coletados em entrevistas à HAMK foram comparados com essas dez abordagens temáticas. Os resultados mostram como a ênfase pedagógica nacional e institucional corresponde no caso da Universidade de Ciências Aplicadas (UAS). A correspondência das diferentes ênfases pedagógicas é classificada como (1) fortemente consolidada, (2) atualmente destacada e (3) menos enfatizada. A conclusão é que é desafiador e complicado estabelecer metas pedagógicas de maneira sistemática, considerando os vários atributos de um mundo em constante mudança. As prioridades internar necessitam da concientização da estratégia, negociações e cooperação. Os pontos principais para o sucesso do desenvolvimento pedagógico são (1) a priorização da ênfase, (2) o progresso sistemático e a garantia de qualidade e (3) a cooperação entre os atores pedagógicos. Palavras-chave: Ensino Superior. Universidade de Ciências Aplicadas. Pedagogia. Estratégia Pedagógica.